A bold and dangerous family : the remarkable story of an Italian mother, her two sons, and their fight against fascism - Moorehead, Caroline (Harper, an imprint of HarperCollins Publishers, 2017)
Mussolini was not only ruthless- he was subtle and manipulative. Black-shirted thugs did his dirty work for him- arson, murder, destruction of homes and offices, bribes, intimidation and the forcible administration of castor oil. His opponents - including editors, publishers, union representatives, lawyers and judges - were beaten into submission. But the tide turned in 1924 when his assassins went too far, horror spread across Italy and twenty years of struggle began. Antifascist resistance was born and it would end only with Mussolini's death in 1945. Among those whose disgust hardened into bold and uncompromising resistance was a family from Florence- Amelia, Carlo and Nello Rosselli. Caroline Moorehead's research into the Rossellis struck gold. She has drawn on letters and diaries never previously translated into English to reveal - in all its intimacy - a family driven by loyalty, duty and courage, yet susceptible to all the self-doubt and fear that humans are prey to. Readers are drawn into the lives of this remarkable family - and their loves, their loyalties, their laughter and their ultimate sacrifice.